Ensino médio politécnico no Rio Grande do Sul : estudo das concepções teóricas e práticas pedagógicas de professores da área das ciências da natureza - Rebello, Ana Paula Santos (2017)
This thesis presents the results of an investigation carried out in the framework of Polytechnic High School, in fourteen public schools in the State of Rio Grande do Sul, Brazil, representing seven mesoregions, gathering testimonies of fourteen teachers with major in Natural Sciences (Chemistry, Physics or Biology) and whose teaching is focused on the space destined to research: Integrated Seminar. Therefore, the general objective of this research was to understand how the theoretical conceptions and pedagogical practices of teachers of Natural Sciences who work in the Integrated Seminary in schools of the seven mesoregions of Rio Grande do Sul deal, in terms of coherence, with the theoretical assumptions of the Polytechnic High School. Research data was obtained through semi-structured interviews with the teachers from these seven mesoregions. Transcribed interviews were treated by Discursive Textual Analysis, per Moraes and Galiazzi (2007). The analysis of the interview responses produced arguments to support that if the EMP model is applied, strategy 3.1 will be reached, encompassing the encouragement of interdisciplinary pedagogical practices that bring theory and practice closer together through the renewal of the curriculum in High School, present in the National Education Plan (BRASIL, 2014). Hence, it verified that the teachers who carry out activities in the Integrated Seminar relate the concepts present in the SEDUC / RS material as part-totality, recognition of knowledge, theory and practice, interdisciplinarity, emancipatory evaluation and research, using them in their pedagogical practices. It can also be concluded that the activities carried out in the Integrated Seminar contribute to the education of the learner, promoting emancipatory aspects and situations that prepare for the labor market. Accordingly, despite some difficulties, such as the lack of continuous training, the need for greater planning time or even poor assistance of the sponsor, it is undoubtedly necessary to continue this study regarding conceptions and practices of teachers, especially in public schools.